Identifikasi Faktor-Faktor Pembentuk Niat Beli Motor Listrik di Indonesia: Pendekatan Exploratory Factor Analysis - Ahmadi (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to identify the key factors that shape purchase intention toward electric motorcycles in Indonesia using an Exploratory Factor Analysis (EFA) approach. The data met the requirements for factor analysis (KMO = 0.831; p < 0.001). The extraction process produced six factors: Value and Utility Orientation, Social Norms and Lifestyle, Marketing-Induced Attitudinal Evaluation, Consumer Experience Quality, Brand Appeal and Product Accessibility, and Consumer Trust. These findings indicate that purchase intention for electric motorcycles is multidimensional, influenced by psychological, social, marketing stimulus, and product accessibility aspects. The results provide a foundational basis for developing confirmatory models and formulating strategies to accelerate electric motorcycle adoption in Indonesia.